MIGRATION IN CAPE VERDE ISLANDS LEGAL AND POLICY FRAMEWORK - Varela Odair Barros; Barbosa Carlos Elias (European Scientific Journal, ESJ, 2014)
This article, in the first place, presents a brief overview of the Cape Verdean emigration, highlighting their route to the West African region. After that it opens the discussion on immigration in Cape Verde, essentially, presenting some data from National Institute of Statistics (NIS), Direction of Foreign and Borders (DBF) and Interministerial Commission for the Study of the Bases and Proposition Immigration Policy (CIMI). It also launches a brief discussion on the challenges of immigration for an insular state like Cape Verde. In the third place, the paper presents the legal framework and the weaknesses in the management of immigration in this country.